Miguel García Monge - Characterisation of Thermal Inertia in University Buildings Using Continuous Temperature Monitoring Data (Jornada de Jóvenes Investigadores del I3A, 2025)
Characterisation of Thermal Inertia in University Buildings Using Continuous Temperature Monitoring Data